Strengthening the role of local governent units in internal security operations - Villena, Dominador T. Jr. (Quezon City National Defense College of the Philippines, 2009)
This study presents the view that the LGU is vital in the long-term resolution of conflict, in its capacity as the capital-building government agency of first resort in communities across the republic. Where the casualty between poverty, grievance, and conflict can be analyzed to determine the dynamics at work, the LGU is in the best position to mediate solutions, in crafting and implementing effective policies aimed at improving quality of life, reducing socio-economic vulnerability, and thereby effectively decreasing the likelihood of political stability. It can only do so, however, by improving efficiency across all levels of government, with the institution of measures to ensure transparency and accountability; the minimization of opportunities for politicized programs; ensuring equal access to capital-building resources; improving targeting of beneficiaries through participative policy-making; designing effective evaluation methods for the results of programs; and reducing areas of redundancy even with the national policy of a "convergence of services". Where these mechanisms are in place, the LGU's roles a strategic instrument of counter-insurgency is made firm.
Thesis (M. in Natinal Security Administration)
Keywords: Internal security -- Philippines -- Padre Burgos (Quezon Province); Local government -- Philippines -- Padre Burgos (Quezon Province); Insurgency -- Philippines